(untitled) (Scientific journal of the Fergana State University, 2025)
This article provides a detailed description and textual analysis of the tazkiras (biographical anthologies) authored by Mirsiddiqkhan Hashmat Bukharayi. The study attempts to examine essential aspects of these works based on original sources and contemporary research. Overall, the article focuses on the characteristics of the tazkiras composed by this poet and writer of the late 19th and early 20th centuries.